Precipitating Factors Contributing Severe Hypoglycemia among Type-2 Diabetic Patients Admitted in a Tertiary Care Hospital of Bangladesh - Rouf, Rushda Sarmin Binte; Pathan, Md Faruque (Bangladesh Journal of Medicine, 2019)
Background: Hypoglycemia is the commonest acute emergency in the diabetic population. This study intends to find out the factors precipitating severe hypoglycemia in type-2 diabetes patients admitted in a tertiary care hospital in Bangladesh. Methods: This cross-sectional study was conducted among 311 diabetic patients admitted in BIRDEM general hospital with hypoglycemia (plasma glucose concentration of <70mg/dl or 3.9mmol/l) with or without altered level of consciousness or neurological recovery of the patient occur after normalization of blood sugar , from a period of March 2014 to April 2015. After obtaining informed written consent a questionnaire focusing on the probable factors of severe hypoglycemia was supplied to the subjects or attendants at bedside. Relevant reports were collected from record book. Results: Mean age of the study respondents was 49.02(±15.99) years which ranged from 18 to 90 years with male predominance (59%). Mean duration of diabetes was 8.5(±5.4) years with range from 3 to 15 years. Majority (85.5%) had more than 6.5% of HbA1c. Severe hypoglycemia was revealed mostly (61.41%) in insulin users. Among them 74(33.5%) and 79(35.7%) patients were using premixed and self mixed regimes respectively. Factors causing severe hypoglycemia were assessed by multivariate analysis. Significant association was found in meal related factors (p<0.001)(missed meal, delayed or inadequate meal), insulin related factors (p<0.001) (Newer dose, miscalculation, faulty technique, defective absorption). Other factors were renal impairment (p<0.001), gastroparesis (p<0.01) and aging (p =0.04). Conclusion: Lifestyle factors are the most important precipitating causes of hypoglycemia. Therefore, appropriate diabetic education including self adjustment and periodic re-evaluation of patient’s knowledge, attitude and practice towards hypoglycemia is of utmost importance to prevent this common but life-threatening complication. Bangladesh J Medicine Jan 2019; 30(1) : 30-34